2016
DOI: 10.1111/psyp.12600
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of graph metrics derived from resting‐state human EEG

Abstract: It is increasingly appreciated that a complete description of brain functioning will necessarily involve the characterization of large-scale interregional temporal synchronization of neuronal assemblies. The need to capture the dynamic formation of such large-scale networks has yielded a renewed interest in the human EEG in combination with a suite of methods for estimating functional connectivity along with the graph theoretical approaches for characterizing network structure. While initial work has establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 40 publications
11
47
0
Order By: Relevance
“…Across the study, we report lower reliabilities for delta, beta and gamma frequency bands than for theta, alpha1, and alpha2 frequency bands. This is in concurrence with several previously mentioned studies in which lower beta and gamma reliabilities (Hardmeier et al, 2014;Jin et al, 2011;Kuntzelman & Miskovic, 2017); and lower delta reliabilities (Deuker et al, 2009;Kuntzelman & Miskovic, 2017) were found. Most commonly, the lower reliability of higher frequency bands is explained by the dichotomy between higher and lower frequency bands, where higher frequency bands are more involved in establishing cognitive representation, while lower frequencies are more anatomically constrained (Bassett & Bullmore, 2006).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Across the study, we report lower reliabilities for delta, beta and gamma frequency bands than for theta, alpha1, and alpha2 frequency bands. This is in concurrence with several previously mentioned studies in which lower beta and gamma reliabilities (Hardmeier et al, 2014;Jin et al, 2011;Kuntzelman & Miskovic, 2017); and lower delta reliabilities (Deuker et al, 2009;Kuntzelman & Miskovic, 2017) were found. Most commonly, the lower reliability of higher frequency bands is explained by the dichotomy between higher and lower frequency bands, where higher frequency bands are more involved in establishing cognitive representation, while lower frequencies are more anatomically constrained (Bassett & Bullmore, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…Lastly, the higher prevalence of muscle artifacts in the higher frequency bands could limit reliability, especially in children. The small‐worldness index (SWI) is also less reliable in our study, which is in concurrence with previous studies (Hardmeier et al, ; Kuntzelman & Miskovic, ). Since small‐worldness is calculated using both clustering coefficient and path length, and both these characteristics vary independently across sessions, a combination of these variances in the SWI (SWI) could contribute to a lower reliability for the SWI.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Relative power was computed as the ratio of the power of the corresponding band and the total power. In the current study, we excluded the gamma band (30–48 Hz) from analysis based on previous evidence suggesting that the gamma frequency range in scalp EEG recordings may be strongly affected by muscle artifact (Whitham et al, 2007), and a recent EEG report indicating low reliability of graph metrics for gamma (Kuntzelman and Miskovic, 2017). …”
Section: Methodsmentioning
confidence: 99%